Georgia state spinal muscular atrophy newborn screening experience: Screening assay performance and early clinical outcomes. Issue 2 (26th September 2022) - Elkins, Kathryn; Wittenauer, Angela; Hagar, Arthur F.; Logan, Rachel; Sekul, Elizabeth; Xiang, Yijin; Verma, Sumit; Wilcox, William R.
Abstract: The purpose of this study is to provide the results of the newborn screening (NBS) program for Spinal Muscular Atrophy (SMA) in the state of Georgia to determine disease incidence, time to diagnosis and treatment, and early outcomes. NBS for SMA was performed using real time PCR assays from February 2019 through February 2020 in a pilot phase of screening. This method continued as part of our official state panel, and here we describe the pilot period as well as the first year of standard screening through February 2021. Medical records of infants with a positive NBS were reviewed for time to confirmation and neurologic evaluation, SMN2 copy number, clinical information, and treatment. Descriptive statistics were applied. Of the 301, 418 samples screened, there were 15 true positive (eight males) and 24 false positive cases. One patient was missed due to human error early in the pilot phase and presented after symptom onset. The incidence of SMA in Georgia is approximately 1 in 18, 840 births per year. After the pilot phase, the false positive rate was found to be so low that all patients who test positive were immediately referred to neurology for further care. Four patients died prior to intervention. Ten patients received intervention. Gene therapy was the preferred treatment. One patient was lost to follow‐up; another was clinically followed. In conclusion, trends for treated patients show improved or stable motor function. Long‐term follow‐up will help determine the durability of treatment.